Assessment Of The Proliferation Rate Of Human Dental Pulp Stem Cells From Permanent And Deciduous Teeth Loaded On Granumas® Scaffold - Nasir, Naseer A. (2011)
Many different human dental stem/progenitor cells have been isolated and characterized such as dental pulp stem cells (DPSCs), stem cells from extracted deciduous teeth (SHED), periodontal ligament stem cells (PDLSCs), stem cells from apical papilla (SCAP), and dental follicle progenitor cells (DFPCs). These post-natal populations have mesenchymal-stem-cell-like (MSCs) qualities, including the capacity for self-renewal and multilineage differentiation potential. The aims of this study were to isolate and characterize both DPSCs and SHED and to determine the expression level of PCNA and Ki-67 by using immunocytochemistry and flow cytometery.